Xinhua Hospital implementation of EMR Project - McFarlan, F. Warren (Franklin Warren); Jia, Ning; Liu, Weiqi; Cao, Shanshan ([London] : SAGE, 2016)
This case study discusses the implementation of the EMR Project at Xinhua Hospital.
Originally Published in: McFarlan, F. W., Jia, N., Liu, W. & Cao, S. (2013). Xinhua Hospital Implementation of EMR Project.5-913-311. Beijing: Tsinghua SEM China Business Case Center.
Description based on online resource; title from home page (viewed on April 27, 2016).
Keywords: elektronické knihy; electronic books; Xinhua Hospital -- Management; Hospitals -- China -- Shanghai -- Administration -- Case studies; Project management -- Case studies; Management information systems -- Case studies; Medical records -- Data processing -- Case studies; Information storage and retrieval systems -- Medical care -- Case studies